2007
DOI: 10.3758/bf03193464
|View full text |Cite
|
Sign up to set email alerts
|

Learning geographical information from hypothetical maps

Abstract: People show biases or distortions in their geographical judgments, such as mistakenly judging Rome to be south of Chicago (the Chicago-Rome illusion). These errors may derive from either perceptual heuristics or categorical organization. However, previous work on geographic knowledge has generally examined people's judgments of real-world locations for which learning history is unknown. This article reports experiments on the learning of hypothetical geographical spaces, in which participants acquired informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…What is less known, however, is when categorical knowledge about real-world geographical entities at several scales (e.g., navigational, global) begins to bias absolute location estimates (but see Kerkman, Friedman, Brown, Stea, & Carmichael, 2003). It is also worth noting that Newcombe and Chiang (2007), who trained people extensively on hypothetical geographic spaces (made-up countries within continents) in order to control for learning history, found that biases in participants' judgments differed from those found in real-world geography. They concluded that the biases in the hypothetical spaces were likely to have been based on perceptual heuristics rather than on categorical organization.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…What is less known, however, is when categorical knowledge about real-world geographical entities at several scales (e.g., navigational, global) begins to bias absolute location estimates (but see Kerkman, Friedman, Brown, Stea, & Carmichael, 2003). It is also worth noting that Newcombe and Chiang (2007), who trained people extensively on hypothetical geographic spaces (made-up countries within continents) in order to control for learning history, found that biases in participants' judgments differed from those found in real-world geography. They concluded that the biases in the hypothetical spaces were likely to have been based on perceptual heuristics rather than on categorical organization.…”
Section: Discussionmentioning
confidence: 99%
“…They particularly address differences between relatively short-term visual memory for dots presented one at a time and longer lasting memories for spatial relations among entities experienced together over much longer time periods (see Friedman, 2009). Thus, the category-adjustment model is constrained, in that it appears to apply primarily to spatial representations in relatively short-term memory; even extensive training on hypothetical maps (Newcombe & Chiang, 2007) did not produce the kinds of category effects seen with real-world geographic and navigable spaces. APPENDIX Each participant's reconstruction of the campus was fit to the actual location, as represented on the map shown in Figure 1.…”
Section: Scale and Research In Spatial Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…At different scales, this might be a group of individuals living in the same neighbourhood, city, state, or country (Golledge and others 1992;Glicksohn 1994;Lloyd 2005a;Huynh and others 2008). The same might also apply to a group of individuals who have learned the same spatial information from a novel cartographic map (Newcombe and Chiang 2007).…”
Section: The Effect Of Competitionmentioning
confidence: 96%
“…The hierarchical organization of psychological space is also documented in other tasks of geographical judgment [for a review, see 10]. The view of perceptual heuristics [11], [13] posits that the biases or distortions occur due to heuristics derived from principles of perceptual organization.…”
Section: Introductionmentioning
confidence: 99%